Kepemimpinan Dan Masa Depan Reformasi Birokrasi Di Indonesia - Novy Setia Yunas (DIMENSI - Journal of Sociology, 2016)
Bureaucracy is the most important part in governance. The position of the bureaucracy which is intersect directly with the public is placing bureaucracy as the main pillars in the public service. However, a very important bureaucraticposition is not offset. By a good performance by the state apparatus is still bound with the old culture and mindset. Moreover, some diseases or pathologies of bureaucracy such actions violate the rules and indiscipline will then make the community more negative perception of the bureaucracy in Indonesia. So with these conditions, the government is committed to implement a process called the bureaucratic reform. Good faith to create the process has lasted long enough, as evidenced by some of the policies that refer to the revamping and arrangement of structures, mechanisms and work culture of bureaucratic organization. However, the process still needs improvement up to now. The process of revision of the bureaucratic reform agenda should be supported by a strong commitment of all the bureaucrats and decisive leadership character and it is able to be control in the implementation of bureaucratic reforms.